Primary carnitine deficiency in a male adult. - Karmaniolas, Konstantinos; Ioannidis, Panagiotis; Liatis, Stavros; Dalamanga, Maria; Papalambros, Theoharis; Migdalis, Ilias (J Med, 2002)
The case is described of a 36 year-old man who presented with progressive proximal muscle weakness and weight loss. His serum creatine phosphokinase (CPK) levels were markedly elevated. The muscle biopsy showed lipid storage myopathy. The muscle carnitine concentration was extremely low (5.6% of normal levels), establishing the diagnosis of myopathic carnitine deficiency. The disorder was considered as primary because there were no indications of any other identifiable condition which could result in a secondary carnitine deficiency. The patient was treated with oral L-carnitine (2 g per day) and showed rapid improvement. Primary myopathic carnitine deficiency is a curable disorder and therefore it should always be considered as a potential diagnosis in cases of myopathy in young adults.
Keywords: Adult; Carnitine; Creatine kinase; Humans; Lipid Metabolism; Male; Muscle Weakness; Muscle, Skeletal; Muscular Diseases